2018
DOI: 10.4103/jisp.jisp_139_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of manual scaling and root planing with or without magnification loupes using scanning electron microscope: A pilot study

Abstract: Aim:The aim of the present study is to compare the amount of remaining calculus, loss of tooth substance, and roughness of root surface after scaling and root planing with or without magnification loupes using scanning electron microscope.Materials and Methods:In the study, 30 teeth indicated for extractions due to severe chronic generalized periodontitis were included in the study. In test Group I, scaling and root planing was performed without magnification loupes, and in test Group II, scaling and root plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The precision was the lowest in preparation without any magnification device. A previous comparative study demonstrated that manual scaling and root planning treatment with magnification loupes could result in less damage to the tooth structure and in less remaining calculus [ 52 ]. However, a recent study compared a total of 30 patients in supragingival debridement with and without using 2.5× magnification loupes [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The precision was the lowest in preparation without any magnification device. A previous comparative study demonstrated that manual scaling and root planning treatment with magnification loupes could result in less damage to the tooth structure and in less remaining calculus [ 52 ]. However, a recent study compared a total of 30 patients in supragingival debridement with and without using 2.5× magnification loupes [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential advantages in wearing loupes, in the current investigation their use was allowed, but not obligatory. However, the benefit of loupes during periodontal treatments is controversially discussed in literature [ 23 27 ], although a better view into the sulcus can be assumed.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative evaluation of scaling and root planning with the use of scanning electron microscopy resulted in more efficiency in removing the calculus than the unaided group. 48 Another study where the evaluation of the effectiveness of scaling and root planning when done using atomic force microscopy and scanning electron microscopy suggested its efficacy. Microanalysis of the root surface identified alteration within cementum when observed under atomic force microscope.…”
Section: Application In Scaling and Root Planningmentioning
confidence: 99%